2016
DOI: 10.1371/journal.pone.0163472
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Sudden Increase in Playing Time on Playing-Related Musculoskeletal Complaints in High-Level Amateur Musicians in a Longitudinal Cohort Study

Abstract: BackgroundSeveral studies in the domain of professional musicians describe the relation between playing time and the occurrence of musculoskeletal complaints in professional musicians. To date, no longitudinal cohort study into this relationship has been performed and no amateur musicians were studied. Therefore, the aim of this study is to examine the causal relationship between a sudden increase in playing time among amateur musicians on the occurrence of musculoskeletal complaints in a prospective cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 15 publications
7
31
0
Order By: Relevance
“…No floor or ceiling effects were found when considering this specific group. Scores reported in the current study were similar to prior reported results in a Spanish conservatory population [26] and correspond with the disability level of highlevel amateur student musicians at the end of an intensive music project [27]. Results of the general DASH questionnaire in this population of music students are comparable with prior reported disability levels of college instrumental musicians [7], and are only somewhat higher than disability levels in young, active adults without complaints [28].…”
Section: Discussionsupporting
confidence: 87%
“…No floor or ceiling effects were found when considering this specific group. Scores reported in the current study were similar to prior reported results in a Spanish conservatory population [26] and correspond with the disability level of highlevel amateur student musicians at the end of an intensive music project [27]. Results of the general DASH questionnaire in this population of music students are comparable with prior reported disability levels of college instrumental musicians [7], and are only somewhat higher than disability levels in young, active adults without complaints [28].…”
Section: Discussionsupporting
confidence: 87%
“…Prevalences of up to 80% have been reported among amateur musicians. [ 8 12 ] These numbers seem to outline the prevalence of musculoskeletal complaints in the open population, for example in the Netherlands a year prevalence of 53.4% is reported in a survey in the open population. [ 13 ] However, no study directly comparing prevalences has been performed to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 11 , 12 ] Playing load is another confirmed risk factor among amateur musicians. [ 8 , 9 , 11 ] A recent cohort study reported a nearly threefold increase in prevalence following a sudden increase in playing time. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%